1992
DOI: 10.1093/nar/20.21.5677
|View full text |Cite
|
Sign up to set email alerts
|

Differentially regulated malate synthase genes participate in carbon and nitrogen metabolism ofS.cerevisiae

Abstract: We have isolated a second gene (MLS1), which in addition to DAL7, encodes malate synthase from S. cerevisiae. Expression of the two genes is specific for their physiological roles in carbon and nitrogen metabolism. Expression of MLS1, which participates in the utilization of non-fermentable carbon sources, is sensitive to carbon catabolite repression, but nearly insensitive to nitrogen catabolite repression. DAL7, which participates in catabolism of the nitrogenous compound allantoin, is insensitive to carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 41 publications
4
80
2
Order By: Relevance
“…Only a weak band was detected in the preparation from glycerol. A similar regulation was reported for the transcription of the gene encoding the malatc synthase isoenzyme functioning in the glyoxylate pathway [17,18].…”
Section: Regulation Of Icll Gene Expressionsupporting
confidence: 75%
“…Only a weak band was detected in the preparation from glycerol. A similar regulation was reported for the transcription of the gene encoding the malatc synthase isoenzyme functioning in the glyoxylate pathway [17,18].…”
Section: Regulation Of Icll Gene Expressionsupporting
confidence: 75%
“…It thus appears that the succinate dehydrogenase complex (SDHC), a tetramer of Sdh1, Sdh2, Sdh3 and Sdh4 (Lombardo et al, 1990;Chapman et al, 1992;Bullis and Lemire, 1994;Daignan-Fornier et al, 1994), is the only TCA cycle-specific enzyme required for acetate utilization on YNBA. Our results also show that the enzymes involved in the glyoxylate cycle operation, such as ACO (Aco1) (Gangloff et al, 1990), malate synthase (Mls1) (Hartig et al, 1992;Kunze et al, 2002), isocitrate lyase (Icl1) (Fernandez et al, 1992;Taylor et al, 1996) and Mdh2 (Minard and McAlister-Henn, 1991), are indispensable for the growth of yeast cells with acetate on YNBA, regardless of their involvement in the TCA cycle. Considering that both the cytoplasmic and mitochondrial isoforms of fumarase (FUM) are encoded by a single gene, FUM1 (Wu and Tzagoloff, 1987), and that operation of the TCA cycle is dispensable on YNBA, as shown above, it is suggested that conversion of fumarate to malate Figure 6.…”
Section: Succinate-fumarate Carrier (Sfc1) Is Essential For Acetate Usupporting
confidence: 54%
“…The first two enzymes, ICL and MLS, are unique to the glyoxylate cycle and are encoded by ICL1 (Fernandez et al, 1992;Taylor et al, 1996) and MLS1 (Hartig et al, 1992;Kunze et al, 2002), respectively. Icl1 is localized solely in the cytosol, even under growth conditions that induce peroxisome proliferation, and its presence in peroxisomes is not essential for a functional glyoxylate cycle (Taylor et al,154 Y. J.…”
Section: Introductionmentioning
confidence: 99%
“…A larger malate synthase may also be found in Succhuromyces cerevisiae according to a transcript revealed under certain specific conditions [25]. Several observations exclude the possibility that the assignment of the larger size for MSG was due to an artifact or sequencing error: (a) the enzyme protein purified from wild-type cells displayed a molecular mass in accordance with that calculated from the corresponding deduced amino acid sequence; (b) the peptide sequence of the N-terminal fragment indicates that the ATG initiation codon is correctly assigned.…”
Section: Discussionmentioning
confidence: 99%